Pemanfaatan Umbi Kentang Hitam Sebagai Media Alternatif Untuk Pertumbuhan Bibit F0 Jamur Tiram dan Jamur Merang - Yusron, Farid Nur, Dra. Suparti, M.Si (2017)
Black potatoes have a high carbohydrate content of 33.7 % so it can be used as an alternative media of PDA. This study aims to know the growth of mycelium of seeding F0 oyster mushrooms and staw mushrooms. The research design was using Completely Randomized Design with factorial pattern consisting of 2 factors: factor 1 is the types of such as extract media, porridge and flour, factor 2 is the type of mushroom such as oyster mushroom and straw mushroom. The analysis used descriptive qualitative and descriptive quantitative method. Based on the result of the research, the average growth of diameter is M1 J1 2cm, M2J1 0,3 cm, M3J12,15 cm, M1J2 3,6 cm, M2J2 7,75 cm, M3J2 8 cm. So it can be concluded that black potato tubers can be used as a medium for growth of seeding F0 oyster mushrooms and staw mushrooms. The best growth on the medium of black potato tuber is black potato tubers flour with the growth of diameter of oyster mushroom mycelium 2.15 cm and straw mushroom 8cm.